2011
DOI: 10.1186/1472-6963-11-1
|View full text |Cite
|
Sign up to set email alerts
|

The quality of care for adults with epilepsy: an initial glimpse using the QUIET measure

Abstract: BackgroundWe examined the quality of adult epilepsy care using the Quality Indicators in Epilepsy Treatment (QUIET) measure, and variations in quality based on the source of epilepsy care.MethodsWe identified 311 individuals with epilepsy diagnosis between 2004 and 2007 in a tertiary medical center in New England. We abstracted medical charts to identify the extent to which participants received quality indicator (QI) concordant care for individual QI's and the proportion of recommended care processes complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(169 citation statements)
references
References 25 publications
9
160
0
Order By: Relevance
“…Twenty to fifty percent of all patients with epilepsy report cognitive problems that can significantly impair daily activities and quality of life (Halgren et al 1991;Vermeulen et al 1993;Perrine and Kiolbasa 1999;Helmstaedter et al 2004;Pugh et al 2011;Kleen et al 2012Kleen et al , 2013. The neurophysiology of seizures and interictal abnormalities, presence of underlying structural abnormalities, such as hippocampal sclerosis, and side effects of antiepileptic medications, can all contribute to cognitive impairment.…”
Section: Cognitivementioning
confidence: 99%
“…Twenty to fifty percent of all patients with epilepsy report cognitive problems that can significantly impair daily activities and quality of life (Halgren et al 1991;Vermeulen et al 1993;Perrine and Kiolbasa 1999;Helmstaedter et al 2004;Pugh et al 2011;Kleen et al 2012Kleen et al , 2013. The neurophysiology of seizures and interictal abnormalities, presence of underlying structural abnormalities, such as hippocampal sclerosis, and side effects of antiepileptic medications, can all contribute to cognitive impairment.…”
Section: Cognitivementioning
confidence: 99%
“…Another systematic review showed that in most parts of the world, complaint rates are low when compared to preventable adverse events; that certain groups use available complaint procedures more than others; and that people are more likely to complain informally than formally [34]. A review of 5,375 patient records from 14 hospitals in the Netherlands compared preventable adverse events with informal and formal patient complaints, medico-legal claims by patients and incident reports by staff [35]. The authors found that only 3.6% of the adverse events identified through review of records was found in these reporting systems.…”
Section: Introductionmentioning
confidence: 99%
“…The body of literature shows that safety culture differs across hospital organisations and depends on organisation experience, size and function. 11,12 …”
Section: Introductionmentioning
confidence: 99%